2018
DOI: 10.1002/syn.22076
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroid allopregnanolone inhibits glutamate release from rat cerebrocortical nerve terminals

Abstract: Allopregnanolone, an active metabolite of progesterone, has been reported to exhibit neuroprotective activity in several preclinical models. Considering that the excitotoxicity caused by excessive glutamate is implicated in many brain disorders, the effect of allopregnanolone on glutamate release in rat cerebrocortical nerve terminals and possible underlying mechanism were investigated. We observed that allopregnanolone inhibited 4‐aminopyridine (4‐AP)‐evoked glutamate release, and this inhibition was prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Allopregnanolone appears to interact with glutamate release, but data are conflicting, with some research showing an inhibitory effect on release, and other research showing a role for allopregnanolone in the induction of glutamate release [32, 33]. Allopregnanolone action in the peripheral nervous system may also have a role in modifying glutamate uptake [34].…”
Section: Resultsmentioning
confidence: 99%
“…Allopregnanolone appears to interact with glutamate release, but data are conflicting, with some research showing an inhibitory effect on release, and other research showing a role for allopregnanolone in the induction of glutamate release [32, 33]. Allopregnanolone action in the peripheral nervous system may also have a role in modifying glutamate uptake [34].…”
Section: Resultsmentioning
confidence: 99%
“…Animal studies have shown that ALLO administration decreases Glu release in specific brain areas [ 46 ]. For example, Hu and colleagues found that ALLO inhibits the release of Glu in rat MPFC, which is our voxel of interest [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the dysfunction of the glutamatergic system is associated with numerous psychiatric conditions, including schizophrenia, depression and anxiety disorders [ 57 ]. Long term administration of olanzapine increases allopregnanolone (that can reduce the release of glutamate) in the rat cerebral cortex and hippocampus [ 58 , 59 ], increases D-aspartate and extracellular L-glutamate in the prefrontal cortex of the mouse [ 60 ], induces a down-regulation of N-methyl-D-aspartate (NMDA) receptors in the caudate and medial and lateral putamen (CPu) and an increase in a-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) receptors in the same areas and a reduction of NMDA receptors in the hippocampal regions CA1 and CA3 [ 61 ]. On the clinical side, the improvement in anxiety symptoms given by olanzapine could be mediated either by a direct anxiolytic effect or indirectly by its efficacy on nuclear symptoms of schizophrenia.…”
Section: Discussionmentioning
confidence: 99%